Nitrogen cycling in a high-nutrient tidal river revealed through high-resolution sampling and nitrate isotope mixing models - Josh Guyat; Douglas R. Tait; James Z. Sippo; Benjamin T. Stewart; Angus Ferguson; James A. Padilla-Montalvo; Christopher Ralph; Jenny Rogers; Merran Griffith; Dirk V. Erler; Michael Ingram; Damien T. Maher (Geochimica et Cosmochimica Acta, 2026)

Overlooked seasonal groundwater nutrient fluxes rival anthropogenic point sources across a variable land‐use tidal river - James A. Padilla‐Montalvo; Douglas R. Tait; Michael J. Reading; Benjamin T. Stewart; Angus Ferguson; Iremar Fernandez‐Vazquez; James Z. Sippo; Shivanesh Rao; Mitch Call; Christopher Ralph; Josh Guyat; Jenny Rogers; et al. (Limnology and Oceanography, 2025)
Understanding groundwater–surface water connectivity in tidal freshwater zones is essential for managing ecosystems within the riverine–estuarine continuum. Groundwater discharge is a key source of dissolved nutrient loads that can lead to eutrophication, deoxygenation, and other ecosystem imbalances in coastal environments. However, groundwater is an often‐overlooked nutrient delivery pathway, with limited studies quantifying groundwater inputs into freshwater transitional zones. Here, we quantify groundwater discharge and its associated nutrient fluxes along a ≈ 75 km section of a tidal freshwater zone within the Hawkesbury–Nepean River (New South Wales, Australia), which is surrounded by multiple land uses. High‐resolution timeseries and spatial surveys were employed over three hydrologically distinct seasons using the naturally occurring radioisotope tracer, radon. Survey results revealed decreasing surface water radon activity and nutrients toward the downstream estuarine boundary. Estimated groundwater discharge rates were highest in the upstream reaches (6.0–12.5 cm d −1 ), regardless of seasonal hydrological dynamics, and decreased downstream, aligning with a reduction in irrigation‐dependent agricultural practices and a change in adjacent catchment morphology. During the dry period, groundwater accounted for up to ≈ 68% of upstream river inputs. Groundwater discharge was also a major source of dissolved inorganic nitrogen, contributing between 0.8 and 1.1 times the inputs from local wastewater treatment plants, and up to 15 times more phosphate than upstream river sources. These findings highlight the role of groundwater discharge as a nutrient driver for tidal freshwater zones, which could have significant implications for future management strategies in these environments.

Benthic Processes are an Important Indicator of Eutrophication in Intermittently Open and Closed Lakes and Lagoons - Angus Ferguson; Giulia Filippini; Jaimie Potts; Ana B. Bugnot; Emma L. Johnston; Shivanesh Rao; Jason Ruszczyk; Katherine A. Dafforn (Estuaries and Coasts, 2024)
Intermittently open and closed lakes and lagoons (ICOLLs) are globally important estuarine systems that are separated from the ocean by a sand beach barrier or berm. The barrier may open or close naturally because of sand and sediment movement or be manually opened by estuarine managers in times of flooding. As intermittently closed systems, it is important to understand the potential for eutrophication and what are the best indicators. This study investigated water quality, sediment quality and benthic processes in four shallow ICOLLs in Sydney, Australia, that experience a range of nutrient loadings. Manly and Curl Curl Lagoons experience higher turbidity and concentrations of pelagic Chl- a compared to Dee Why and Narrabeen Lagoons. They also differ with respect to general morphology with Manly and Narrabeen deeper and more linear while Curl Curl and Dee Why are shallower and more circular. Relationships between nutrient loading and traditional water quality indicators of eutrophication such as chlorophyll- a , turbidity and dissolved oxygen appeared to be moderated by lagoon morphology and hydrology, which control the ratio of pelagic to benthic production and net accumulation of sediment organic matter. We found that all the lagoons investigated were net heterotrophic, with Narrabeen and Manly the least and the most heterotrophic respectively. Ratios of total organic carbon (TOC):benthic community respiration (CR) varied among lagoons and were likely related to the dominance of refractory organic matter in Narrabeen (~ 99%), and more labile organic matter in Manly and Curl Curl Lagoons (~ 90%). Benthic community respiration increased with nutrient loading rates across the lagoons, suggesting that benthic processes are a critical indicator of eutrophication in these shallow systems. In contrast to the generalised conceptual model of eutrophication in coastal systems whereby nutrient pollution causes a reduction in benthic primary productivity at the expense of increased pelagic primary productivity, our results suggest that benthic microalgal productivity in shallow ICOLLs plays an important role in buffering against eutrophication of the water column but may also contribute to organic enrichment of sediments.

Extreme iron cycling in a coastal lake-lagoon system driven by interactions between climate and entrance management - Scott G. Johnston; Thor Aaso; Damien T. Maher; Edward D. Burton; Mitchell Call; Mathew Birch; John Schmidt; Angus Ferguson (Science of The Total Environment, 2024)

Nitrogen-cycling genes in oyster reefs and surrounding sediments: Relationships with environmental factors and respective nitrogen rates - Giulia Filippini; Ana B. Bugnot; Deepa R. Varkey; Nachshon Siboni; Angus Ferguson; Paul E. Gribben; Katherine Erickson; Julia Palmer; Katherine A. Dafforn (Marine Pollution Bulletin, 2023)

The influence of oyster reefs and surrounding sediments on nitrogen removal – An in-situ study along the East coast of Australia - Giulia Filippini; Ana B. Bugnot; Angus Ferguson; Paul E. Gribben; Julia Palmer; Katherine Erickson; Katherine A. Dafforn (Environmental Research, 2023)

Light history-dependent respiration explains the hysteresis in the daily ecosystem metabolism of seagrass - Matthew P. Adams; Angus J. P. Ferguson; Paul S. Maxwell; Brodie A. J. Lawson; Jimena Samper-Villarreal; Katherine R. O’Brien (Hydrobiologia, 2016)

Carbon and Nitrogen Cycling in a Shallow Productive Sub-Tropical Coastal Embayment (Western Moreton Bay, Australia): The Importance of Pelagic–Benthic Coupling - Angus J. P. Ferguson; Bradley D. Eyre (Ecosystems, 2010)

Denitrification efficiency for defining critical loads of carbon in shallow coastal ecosystems - Bradley D. Eyre; Angus J. P. Ferguson (Hydrobiologia, 2009)